Apprehending felt futures in Broome, Australia. Issue 106 (November 2019) - Kelly, David
Abstract: This paper demonstrates how the atmospheres of place act upon bodies, provoking thought and mediating the emergence of a more-than- human politics for living in the urban Anthropocene. Taking-place in a remote urban town, it explores the conditioning geographies of Indigenous-led activisms that harness the potential of place in recent political projects. Central to this is a thinking-with Indigenous felt approaches to place, specifically the work of Country as: a concept that maps geographies of belonging, co-existence and reciprocity; a living body that has the capacity to affect and be affected; and, an force that is felt as a diffuse-yet-palpable atmosphere. Through the narratives of Indigenous activists, this paper describes spacetimes of being-with- Country that dwell in the atmospheres and apprehend capacities to act upon and imagine other present-futures. To think of an environmental agent animated by the force of liveliness, is to work through the political status of the non-human, all the while experimenting and making a call for attention to the felt reality of human connection.